2013
DOI: 10.1038/nature12488
|View full text |Cite
|
Sign up to set email alerts
|

Uhrf1-dependent H3K23 ubiquitylation couples maintenance DNA methylation and replication

Abstract: Faithful propagation of DNA methylation patterns during DNA replication is critical for maintaining cellular phenotypes of individual differentiated cells. Although it is well established that Uhrf1 (ubiquitin-like with PHD and ring finger domains 1; also known as Np95 and ICBP90) specifically binds to hemi-methylated DNA through its SRA (SET and RING finger associated) domain and has an essential role in maintenance of DNA methylation by recruiting Dnmt1 to hemi-methylated DNA sites, the mechanism by which Uh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

20
396
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 344 publications
(416 citation statements)
references
References 34 publications
20
396
0
Order By: Relevance
“…Our study unravels unexpected interactions between LMO2 and three essential replication proteins, MCM6, PRIM1, and POLD1 (30), as well as chromatin-modifying enzymes that have wellcharacterized roles in DNA replication, BAZ1A, SETD8, MYST2, and UHRF1 (31)(32)(33)47). More importantly, tethering LMO2 to DNA via the GAL4-DNA binding domain was sufficient to recruit MCM5 and POLD1 to DNA and to transform UAS into origins of replication, indicating that LMO2 directly controls DNA replication.…”
Section: Discussionmentioning
confidence: 67%
“…Our study unravels unexpected interactions between LMO2 and three essential replication proteins, MCM6, PRIM1, and POLD1 (30), as well as chromatin-modifying enzymes that have wellcharacterized roles in DNA replication, BAZ1A, SETD8, MYST2, and UHRF1 (31)(32)(33)47). More importantly, tethering LMO2 to DNA via the GAL4-DNA binding domain was sufficient to recruit MCM5 and POLD1 to DNA and to transform UAS into origins of replication, indicating that LMO2 directly controls DNA replication.…”
Section: Discussionmentioning
confidence: 67%
“…Importantly, genome-wide association studies of Crohn's disease and ulcerative colitis patients have identified SNPs near UHRF1, DNMT1, and DNMT3a (37,38), suggesting that alterations in these genes may lead to IBD. Although alternative roles for UHRF1 including cell cycle regulation and histone ubiquitylation have been identified (39)(40)(41), up-regulation of tnfa in the intestine of both uhrf1 pd1092 and dnmt1 pd1093 mutants strongly suggests that it is the loss of DNA methylation at CpG dinucleotides at the tnfa promoter that leads to elevated tnfa expression.…”
Section: Discussionmentioning
confidence: 99%
“…The SRA (SET and RING fingerassociated) domain of Uhrf1 specifically recognizes hemimethylated CpG and flips the methylated cytosines out of double-stranded DNA (17)(18)(19). Recently, it was reported that Dnmt1 recognizes ubiquitylated lysine 23 of histone H3, which is catalyzed by the RING finger E3 ligase activity of Uhrf1 and is a necessary step for maintenance methylation (20).…”
mentioning
confidence: 99%